The spatial dynamics of the Semarang-Surakarta development corridor: two young metropolitan cities of Central Java, Indonesia. (2nd March 2022) - Buchori, Imam; Rahmayana, Lintang; Sejati, Anang Wahyu; Pangi, Pangi; Basuki, Yudi; Pramitasari, Angrenggani
The interactions between metropolitan cities can generate so-called development corridors along the regional lines. In Central Java, three cities, namely Yogyakarta (Jogya), Surakarta (Solo), and Semarang, form a triangular development known as Joglosemar. This study aimed to observe the spatial dynamics of the Semarang-Surakarta corridor, regarding the operation of the new toll road connecting these two cities. Spatial analyses based on the geographic information system (GIS) were applied to observe the land-use change in the corridor. Statistical analyses focused on population shift, the poor, and employment at the sub-district (kecamatan) level. The empirical findings confirm previous studies, in that the regional development follows regional lines along both arterial and toll roads, and the existence of the toll road was the magnet for the development. However, the increase in industrial activities did not always benefit the poor, especially in the sub-districts where industrial activities have been developing in the longer term. For this reason, we recommend that local governments consider how to make the positive impacts of industrial development sustainable. The results of this study are also expected to enrich the literature on the spatial dynamics of a development corridor connecting two medium-sized metropolitan cities in developing countries.